Drama and Theater as Practical in 2nd and 3rd Cycles of Basic Education – a Study in the Region of Coimbra - Figueira, Ana Paula Couceiro (2011)
As related by Efland (1990), the framing and increment of the art in education are, not only, related with the general education, but also under its influence. Therefore, throughout the years, the inclusion or exclusion of art in curricula has beena consequence of scientific, philosophical and political transformations and evolutions. Conceptions and perspectives that justify art in education, not always consonant in its conceptualization, exemplify the complexity of the subject. Following those ideas, the present article, summary of the master thesis A expressão dramática/teatro como prática nos 2.º e 3.º ciclos do ensino básico is intended to reveal the drama teachers’ understanding of the importance and significance of artistic expressions for theatre and drama related activities at Junior High School.